Employment Of Quranic Evidence In The Book Al-Iqtisad Fi Sharh Al-Intiqad By Muhammad Ibn Mustafa Al-Aishi An Applied Study/ آلية التوظيف الحجاجي للشواهد القرآنية في كتاب الاقتصاد في شرح الانتقاد لمحمد بن مصطفى العيشي دراسة تطبيقية - Sarah Hatem Musa; Khalil Ibrahim Allawi (Ijaz Arabi Journal of Arabic Learning, 2026)
The research dealt with the mechanism of the argumentative employment of Quranic evidence in the book “Al-Iqtisad fi Sharh Al-Intiqad” by Muhammad bin Mustafa Al-Aishi. This research revealed a new grammatical figure who was not mentioned in printed grammar books, and this is a new addition to the Arabic grammatical library. The research demonstrated an important phenomenon, which is the argumentative employment of Quranic evidence by a scholar of the eleventh century AH. The research demonstrated Al-Aishi’s method of citing Quranic evidence through a clear mechanism. Al-Aishi employed Quranic evidence to document grammatical rules, establish grammatical rulings, and give preference between the readers mentioned in grammatical disagreement. In addition, Al-Aishi took the Quranic evidence as evidence to respond to and object to those who disagreed with him, since the Quranic evidence is one of the strongest pillars of the Arabic language, and in doing so, he benefits from the strongest grammatical evidence. The research relied on the descriptive analytical approach based on describing and analyzing the phenomenon according to Al-Aishi. The features of the mechanism of using the Qur’anic evidence became clear, which is manifested in the multiplicity of Qur’anic evidence in one issue, in addition to the questions that are assumed when using the Qur’anic evidence and answering those assumptions, and employing the Qur’anic evidence in a clear scientific.